Populism, a Thread and a Chance. Between Demagogy and Participation - Cristiano Gianolla (SocietàMutamentoPolitica: Rivista Italiana di Sociologia, 2017)
This paper inquiries into the concept of populism from a sociological perspective. This is done by highlighting the unstable co-presence of demagogy and participation through an intercultural analysis of the European and the Indian discursive approach and its construction of popular politics. The underlying understanding is that the concept is misrepresented by the equation of populisms with demagogy. The paper therefore builds on “participatory populism” to promote the expansion, rather than contraction, of the term’s ambiguity. The analysis accounts for the emergence of populisms as subaltern politics that are unable to subvert the political status quo but are able to enhance it morally. The study starts by problematizing the concept’s historical double movement that is at the basis of its demagogic and participatory features, then it focuses on populism as a signifier reinforced by the impasse between the two pillars of liberal democracy. Furthermore, by critically building on Laclau’s position, its social discursive formation is investigated. Chatterjee’s “political society” and the party-movements (the Aam Aadmi Party and the Movimento 5 Stelle) are two contradictory cases that are proposed to exercise an expansion of the concept.